2016
DOI: 10.1111/jcpp.12647
|View full text |Cite
|
Sign up to set email alerts
|

Food fussiness and food neophobia share a common etiology in early childhood

Abstract: Background‘Food fussiness’ (FF) is the tendency to be highly selective about which foods one is willing to eat, and emerges in early childhood; ‘food neophobia’ (FN) is a closely related characteristic but specifically refers to rejection of unfamiliar food. These behaviors are associated, but the extent to which their etiological architecture overlaps is unknown. The objective of this study was to quantify the relative contribution of genetic and environmental influences to variation in FF and FN in early chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 40 publications
7
78
1
2
Order By: Relevance
“…3,7,9,15 In the present study, picky eaters with behaviors related to choosing a limited variety of foods had a lower quality of diet for some micronutrients, but not energy. 16 Birch and Marlin found that as the number of exposures to a food increased, the child's preference for that food increased.…”
Section: Discussionmentioning
confidence: 46%
“…3,7,9,15 In the present study, picky eaters with behaviors related to choosing a limited variety of foods had a lower quality of diet for some micronutrients, but not energy. 16 Birch and Marlin found that as the number of exposures to a food increased, the child's preference for that food increased.…”
Section: Discussionmentioning
confidence: 46%
“…Data from the Gemini twin study (2402 families; 4804 twins) showed that both EOE and EUE are shaped primarily by the shared family environment, not by genes, in early childhood. This contrasts strongly with other eating behaviours found to be under substantial genetic control in early life . Replication is an essential part of scientific progress , and here we aimed to verify the strong environmental component to child EOE and EUE in a sample selected for high and low obesity risk.…”
Section: Introductionmentioning
confidence: 91%
“…nutritional benefit vs. risk of harm). Moreover, this food group order is seen in the susceptibility of foods to fussiness and neophobia [13] or, in reverse, to food enjoyment: thus, it is not surprising that there is evidence for genetic influence on these eating tendencies (see below) [14][15][16]. By comparison, a recent study of 2865 twins aged 18-19 years [17] found that, as children grow into young adults and experience increasing independence in eating and food choice, the unique environment experienced by each individual becomes more influential on preference patterns within food groups, although heritability still has a moderate influence, ranging from 32% to 54% across food groups.…”
Section: Genetic Influencesmentioning
confidence: 99%